System for Efficacy and Cytotoxicity Screening of Inhibitors Targeting Intracellular Mycobacterium tuberculosis - Zheng, Xingji (J Vis Exp, 2017)
Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), is a leading cause of morbidity and mortality worldwide. With the increased spread of multi drug-resistant TB (MDR-TB), there is a real urgency to develop new therapeutic strategies against M. tuberculosis infections. Traditionally, compounds are evaluated based on their antibacterial activity under in vitro growth conditions in broth; however, results are often misleading for intracellular pathogens like M. tuberculosis since in-broth phenotypic screening conditions are significantly different from the actual disease conditions within the human body. Screening for inhibitors that work inside macrophages has been traditionally difficult due to the complexity, variability in infection, and slow replication rate of M. tuberculosis. In this study, we report a new approach to rapidly assess the effectiveness of compounds on the viability of M. tuberculosis in a macrophage infection model. Using a combination of a cytotoxicity assay and an in-broth M. tuberculosis viability assay, we were able to create a screening system that generates a comprehensive analysis of compounds of interest. This system is capable of producing quantitative data at a low cost that is within reach of most labs and yet is highly scalable to fit large industrial settings.